2014
DOI: 10.1128/jvi.00320-14
|View full text |Cite
|
Sign up to set email alerts
|

The Histone Deacetylase Inhibitor Vorinostat (SAHA) Increases the Susceptibility of Uninfected CD4 + T Cells to HIV by Increasing the Kinetics and Efficiency of Postentry Viral Events

Abstract: Latently infected cells remain a primary barrier to eradication of HIV-1. Over the past decade, a better understanding of the molecular mechanisms by which latency is established and maintained has led to the discovery of a number of compounds that selectively reactivate latent proviruses without inducing polyclonal T cell activation. Recently, the histone deacetylase (HDAC) inhibitor vorinostat has been demonstrated to induce HIV transcription from latently infected cells when administered to patients. While … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
55
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 54 publications
3
55
0
Order By: Relevance
“…SAHA may successfully increase viral transcription, but fails to effectively enhance viral translation61. Moreover, SAHA treatment may increase susceptibility of uninfected CD4 T cell to HIV, and impair virus-specific CTLs6263. In comparison, synthetic analogues of protein kinase C (PKC) agonists represent HIV latency reversing agents (LRAs) of interest.…”
Section: Discussionmentioning
confidence: 99%
“…SAHA may successfully increase viral transcription, but fails to effectively enhance viral translation61. Moreover, SAHA treatment may increase susceptibility of uninfected CD4 T cell to HIV, and impair virus-specific CTLs6263. In comparison, synthetic analogues of protein kinase C (PKC) agonists represent HIV latency reversing agents (LRAs) of interest.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous in vitro, ex vivo, and clinical studies have shown that HDACi reactivate latent HIV infection (9, 12-16, 37, 38, 40-48). However, a theoretical concern is that HDACi-induced viral production in cART sanctuary sites could result in de novo HIV infections and reseeding of the latent reservoir (17,18). In the present study, we addressed this concern by comprehensively exploring the impact of romidepsin on HIV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Lucera et al reported that supraphysiological concentrations (200 nM) of romidepsin increased the susceptibility of CD4 ϩ T cells to HIV infection (17). These data, as well as those of others (18), raise the concern that inducing latent HIV in anatomical compartments with suboptimal cART concentrations (19) could lead to the infection of new target cells and reseeding of the latent reservoir.…”
mentioning
confidence: 89%
“…However, a major clinical concern with this strategy is that, although administered in the context of cART, infection of new uninfected CD4 ϩ T cells and macrophages by induced virus during periods of viral activation from latency may occur. Indeed, a recent study has demonstrated that although vorinostat does not affect virus-CD4 ϩ T cell fusion, it increases the kinetics of post-entry events such as reverse transcription and integration thereby promoting productive infection of CD4 ϩ T cells and potentially reseeding the viral reservoirs being purged (4). Another important HIV reservoir is the macrophage.…”
mentioning
confidence: 99%